Keanekaragaman Serangga Sebagai Pakan Alami Katak Tegalan (Fejervarya limnocharis, Gravenhorst) pada Ekosistem Sawah di Desa Panggungharjo, Kecamatan Sewon, Kabupaten Bantul - Farid Kuswantoro; R.C. Hidayat Soesilohadi (Universitas Gadjah Mada, 2016)
Paddy field was a dynamic and biodiversity rich ecosystems. Insect diversity in paddy field ecosystem was infected by paddy plant growth stages. Grass frog (Fejervarya limnocharis) ate insects as their natural prey. Insect population dynamics during vegetative, generative and reproductive stage of paddy plants infected F. limnocharis natural prey. This research aims were to study insect diversity and F. limnocharis insect prey diversity of vegetative, reproductive and generative paddy plant growth stages at Panggungharjo village, Sewon, Bantul. Insect sampling was conducted by direct survey method while F. limnocharis collection conducted by Visual Encounter Survey (VES) method. Ninety eight insect species from 51 different families and nine orders of insect were found. The orders were Coleoptera, Diptera, Hymenoptera, Odonata, Orthoptera, Dictyoptera, Dermaptera, Hemiptera and Lepidoptera. Stomachs analysis indicated F. limnocharis ate nine insect orders. The orders were Coleoptera, Diptera, Hymenoptera, Orthoptera, Dictyoptera, Dermaptera, Hemiptera, Lepidoptera and Isoptera. Most commonly insect prey in vegetative, reproductive and generative phase paddy growth stage were the members of the Order Coleoptera, Family Acrididae (Orthoptera) and Family Formicidae (Hymenoptera) respectively. This study concluded F. limnocharis main natural prey was the easily found and easily perceived insects.